The impact of electoral reform on the public service: the New Zealand case - Boston, Jenathan et al. (1998)
October 1996 marked the beginning of a new era in New Zealand politics, with the advent of a system of proportional representation based on the German model. This article explores the impact of electoral reform on the public service. First, it summarises the extensive public sector reforms during the mid-to-late 1980s and considers the preparations undertaken by the public service for proportional representation. Second, it outlines the concerns and expectations about the likely consequences of the new electoral system on the bureaucracy. Third, against this background, the article examines the extent to which the public service has been affected by electoral reform. It is argued that despite some notable changes to the political environment within which officials operate, the overall impact of proportional representation on the public service to date has been modest. The analysis presented here is based on a series of interviews conducted during 1997 with ministers, senior public servants, ministerial advisers and parliamentary officials, along with a range of secondary sources. - Reproduced
Keywords: Elections - New Zealand; Public administration - New Zealand; Civil service